2019
DOI: 10.14814/phy2.13975
|View full text |Cite
|
Sign up to set email alerts
|

Augmented contractility of murine femoral arteries in a streptozotocin diabetes model is related to increased phosphorylation of MYPT1

Abstract: Diabetes mellitus (DM) is a metabolic disorder with high prevalence, and a major risk factor for macro‐ and microvascular abnormalities. This study was undertaken to explore the mechanisms of hypercontractility of murine femoral arteries (FA) obtained from mice with streptozotocin (STZ)‐induced diabetes and its relation to the phosphorylation profile of the myosin phosphatase target subunit 1, MYPT1. The immunoreactivity of MYPT1 toward phospho‐MYPT1‐T696, MYPT1‐T853, or MYPT1‐S695, used as a read out for MYPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 58 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Different approaches have been used to measure IVC diameters for proper filter placement. For example, a radioopaque ruler fixed behind the patient, calibrated intravascular catheter methods, and subtraction of 20 % from the measured transverse IVC diameter on radiography [13,14]. A recent study also suggested that IVC circular geometry using cross-sectional CT should be considered in the measurement of IVC, since the IVC assumes a circular shape after the placement of the filter [13].…”
Section: Discussionmentioning
confidence: 99%
“…Different approaches have been used to measure IVC diameters for proper filter placement. For example, a radioopaque ruler fixed behind the patient, calibrated intravascular catheter methods, and subtraction of 20 % from the measured transverse IVC diameter on radiography [13,14]. A recent study also suggested that IVC circular geometry using cross-sectional CT should be considered in the measurement of IVC, since the IVC assumes a circular shape after the placement of the filter [13].…”
Section: Discussionmentioning
confidence: 99%
“…As well, augmented vascular contractility (Xie et al, 2006;Matsumoto et al, 2014;Lubomirov et al, 2019), increased vascular inflammation (Zhang et al, 2008;Ku and Bae, 2016), and stimulated endothelial cells apoptosis (Sheu et al, 2005, Sheu et al, 2008 can cooperate to cause vascular dysfunction (Figure 1A). There are key processes in obesity which collaborate and lead to impairment of vascular function.…”
Section: Vascular Complications Of Diabetes and Obesitymentioning
confidence: 96%